The family remains [compact disc, unabridged] - Jewell, Lisa (Simon & Schuster Audio, 2022)
When Rachel Rimmer₂s phone rings in the early morning, she is shocked when she hears her husband₂s housekeeper sobbing on the line. Her husband, Michael, has been found dead in the cellar of his house in France and all signs point to murder. The French police conclude that Michael was killed by his gangster associates. They have no idea that the real killer is still out there: his ex-wife, Lucy. A year later, she and her children are happily living in London, unaware that Rachel is on the hunt for her. She may have never met this woman, but Rachel knows Lucy was the last person to see her husband alive. And there is nothing that is going to stop her from discovering the truth.